Prenatal Development of Pinna in Indian Sheep - Karunasri V,; Nagamalleswari Y,; Raju N K B,; Sreenu M, (Indian Journal of Veterinary Anatomy, 2026)
Gross and microanatomical studies of pinna were conducted in embryos and fetuses collected from Nellore sheep aged between 22 to 145 days. External ear comprised of pinna (Auricle) and external acoustic meatus. Morphogenesis revealed that the otic placode and four pairs of pharyngeal pouches were visible externally in the ventro-lateral aspect of neck region by 22 days. Five aural hillocks were appeared at 23 days. Auricle shifted its position from neck to temporal region by 63 days. The pinna presented 5-6 prominent ridges by 74 days. Histogenesis revealed that the first and second pharyngeal arches developed with an intervening first pharyngeal cleft by 22 days. Small cone shaped pinna at 24 days modified into irregular sigmoid shaped structure with mesenchymal condensation at the centre of the auricle in 31 days embryos. Differentiation of hair follicles was first initiated on the auricular epidermis by 69 days and presence of elastic cartilage in the center of pinna by 80 days. Biometric analysis of pinna revealed that the average length, width increased significantly between different age groups. It may be concluded that the development of pinna continues postnatally also in sheep.